Beyond the fear: Nurses' experiences caring for patients with Middle East respiratory syndrome: A phenomenological study. Issue 17 (23rd June 2020) - Lee, Jin Young; Hong, Jeong Hee; Park, Eun Young
Abstract: Aim and objectives: To explore the experiences of Korean nurses who had directly cared for patients with Middle East respiratory syndrome (MERS) and to derive the structure and meaning of these experiences. Background: In 2015, the MERS epidemic struck Korea, and ill‐prepared nurses had to care for patients with MERS. Nurses experienced conflict between their fear of the disease and their work and professional ethic. Design: We employed a phenomenological qualitative approach. Methods: Inductive, qualitative, in‐depth interviews were performed with 17 nurses. The study process followed the Consolidated Criteria for Reporting Qualitative Research (COREQ) checklist. Results: The qualitative inductive content analysis generated seven theme clusters and 18 themes. The theme clusters were "Fear of Uncertainty, " "Beyond Hesitation, " "A Scene Like a Battlefield, " "Chaotic Nursing Identity, " "Buttresses for Sustainability, " "Lingering Trauma" and "Expanded Horizon of Nursing." The final analysis revealed that the core theme was "Beyond the fear of uncertainty." Conclusions: This study contrives a more in‐depth, holistic understanding by describing the experiences of nurses who directly cared for patients with MERS—the first large‐scale infectious disease in Korea. Although nurses saw themselves as vital caregivers, they were frightened of the disease, had to work in a harsh environment, experienced various internal conflicts and had to deal with varying forms of uncertainty. Relevance to clinical practice: This study sheds light on the nursing situation during crises involving serious infectious diseases; to combat these, more medical facilities are needed, and staff should be proactively guided on how to care for patients. It can serve as part of a good foundation for further study of medical staff during recurring epidemics.